An (slightly) innovative vehicle for urban ground transport - Kruszyna, Maciej (Przegląd Komunikacyjny)
The article presents a proposal for constructing a vehicle for urban ground transport using a tram system (current consumption from the catenary, separate tracks), but with the option of leaving the track and using batteries or charging stations. This will allow for temporary or target extension of existing routes and for bringing large-scale rolling stock to densely built-up housing estates. Based on the review of modern solutions, the thesis was formulated that the development of an (slightly) innovative vehicle is "at your fingertips." The possibilities of introducing new rolling stock were shown on the example of Wroclaw. Nevertheless, the proposed solution may also be attractive to other, at least Polish cities. Keywords: Tram; Trolleybus; Electric bus, Innovation